From Nablus to Gaza: Exploring the Structure and Identity of Palestinian Arabic - Jurakulova Yokutoy (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article offers a comprehensive linguistic overview of the Palestinian dialect of Arabic, a major variety within the Levantine dialect group. The study examines its phonological system, morphological patterns, and syntactic structures, with a focus on authentic examples drawn from everyday speech. Special attention is given to the interaction between colloquial and formal Arabic in Palestinian usage, and to morphological features such as vowel shortening when suffixes are added to verb roots (e.g., baqūl → baqul-lak). In the final section, the article addresses a pressing issue in Arabic dialectology: the absence of a standardized grammar or writing system for Palestinian Arabic. The author proposes a foundational model for standardization based on central urban varieties, supported by corpus development and community-informed documentation. This approach is intended to support future educational use and technological applications such as automatic translation and voice recognition.